2018
DOI: 10.1038/s41467-018-06366-z
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic adrenocortical carcinoma displays higher mutation rate and tumor heterogeneity than primary tumors

Abstract: Adrenocortical cancer (ACC) is a rare cancer with poor prognosis and high mortality due to metastatic disease. All reported genetic alterations have been in primary ACC, and it is unknown if there is molecular heterogeneity in ACC. Here, we report the genetic changes associated with metastatic ACC compared to primary ACCs and tumor heterogeneity. We performed whole-exome sequencing of 33 metastatic tumors. The overall mutation rate (per megabase) in metastatic tumors was 2.8-fold higher than primary ACC tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 53 publications
1
45
0
Order By: Relevance
“…This is considered a hallmark of cancer and provides selective advantage for the survival of tumour cells either in a dormant phase or as a rapidly progressing disease (Jin et al 2018). Tissue heterogeneity in melanoma is key to the survival and evolutionary versatility of the disease (Hwang et al 2018), and some clinical studies have shown that reduced heterogeneity is linked to a longer survival of the cancer patients (Gara et al 2018;Hanahan and Weinberg 2011;Szász et al 2017). To some extent, heterogeneity exists in all types of malignant tumours.…”
Section: Pathological Characterisation Of Melanomamentioning
confidence: 99%
“…This is considered a hallmark of cancer and provides selective advantage for the survival of tumour cells either in a dormant phase or as a rapidly progressing disease (Jin et al 2018). Tissue heterogeneity in melanoma is key to the survival and evolutionary versatility of the disease (Hwang et al 2018), and some clinical studies have shown that reduced heterogeneity is linked to a longer survival of the cancer patients (Gara et al 2018;Hanahan and Weinberg 2011;Szász et al 2017). To some extent, heterogeneity exists in all types of malignant tumours.…”
Section: Pathological Characterisation Of Melanomamentioning
confidence: 99%
“…This gene has been associated with myeloproliferative disorders, as shown by its fusions with platelet-derived growth factor receptor beta gene (PDGFRB) [33]. In addition, PDE4DIP variants are one of the most frequent in metastatic adrenocortical carcinomas in adults [34]. Of note, all four of our patients with an inactivating variant in PDE4DIP also harbor the hypomorphic widespread TP53 p.R337H founder allele [35][36][37].…”
Section: Discussionmentioning
confidence: 74%
“…It is intriguing to note that a recent study of metastatic ACC tumours has identified an enrichment of driver mutations in RA pathway genes, possibly lending further support to the inactivation of this pathway being a crucial step in ACC progression. 56 In addition, alterations in the retinoic acid pathway have also been linked recently to benign adrenocortical tumours secreting aldosterone. 57 In conclusion, our results offer human genetic evidence for the importance of the druggable RA pathway in ACC onset and extend its relevance to progression of both paediatric and adult ACC.…”
Section: Discussionmentioning
confidence: 99%